Persisting symptoms and duodenal inflammation related to Giardia duodenalis infection - Hanevik, Kurt; Hausken, Trygve; Morken, Mette Helvik; Strand, Elisabeth Astrup; Mørch, Kristine; Coll, Peter; Helgeland, Lars; Langeland, Nina (The Journal of infection, 2007)
After a large waterborne outbreak of Giardia infection in Bergen, some patients experienced persisting abdominal symptoms despite metronidazole treatment. This study aimed at investigating possible causes for their symptoms. Over a 15 months period, 124 referred patients were evaluated in a prospective cohort analysis with a standardised investigation including duodenal biopsies and aspirate, blood tests and faecal parasite and calprotectin tests. Recovered subjects were recruited for symptom analysis. Persisting Giardia duodenalis infection was found in 40 patients (32.3%). Duodenal biopsies showed signs of inflammation in 57 patients (47.1%). Microscopic duodenal inflammation was present in 34 (87.2%) of the Giardia positive and 23 (28.0%) of the Giardia negative patients. There were significant associations between persistent Giardia positivity, microscopic duodenal inflammation and a positive calprotectin test. Duodenal aspirate and duodenal biopsies performed poorly in diagnosis of persistent giardiasis. In patients with persisting symptoms after metronidazole treated Giardia infection we commonly found chronic Giardia infection and microscopic duodenal inflammation, especially in illness duration less than 7 months. Both these findings subsided over time. Increasingly, investigations could not determine a definite cause for the persistent symptoms. The very long-term post-giardiasis diarrhoea, bloating, nausea and abdominal pain documented here need further study.